PANDANGAN ESKATOLOGI TENTANG AMILLIANISME, POSTMILLIANISME, DAN PREMILLIANISME - Yakub Hendrawan Perangin Angin; Tri Astuti Yeniretnowati (STT Bethel The Way, 2021)
A phenomenon that still often occurs among Christians is the existence of debates when discussing the millennial kingdom, which often ends in disputes and even sharp and deep divisions between fellow Christians and the church and even the synod. The aim of this research is to provide Christians with a balanced perspective in looking at the various views that exist regarding the millennial kingdom. The research method used is literature research, where the researcher collects various textbooks and analyzes various views related to the millennial kingdom and examines the relationship and compatibility with the writing theme so that the results of the study of Eschatological views on Amillianism, Postmillianism, and Premillianism are compiled into conceptual views. Eschatology. The result of this research is that every view of the millennial kingdom must be tested by referring back to the full biblical data, where Bible verses are reinterpreted by the Bible as a whole. It can be concluded that teaching regarding Amillianism, Postmillianism, and Premillianism is adapted to the context of church denominational doctrine.